2020
DOI: 10.1167/jov.20.8.20
|View full text |Cite
|
Sign up to set email alerts
|

Encoding perceptual ensembles during visual search in peripheral vision

Abstract: Observers can learn complex statistical properties of visual ensembles, such as their probability distributions. Even though ensemble encoding is considered critical for peripheral vision, whether observers learn such distributions in the periphery has not been studied. Here, we used a visual search task to investigate how the shape of distractor distributions influences search performance and ensemble encoding in peripheral and central vision. Observers looked for an oddly oriented bar among distractors taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…Many studies have shown that observers respond slower when a test target is similar to previous distractors with the degree of slowing monotonically related to the shape of distractor distributions. This is indeed what we found in our previous studies 24 28 , 43 . We refer to the test target position in the feature space as the current-target to previous distractor-distance (CT-PD).…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Many studies have shown that observers respond slower when a test target is similar to previous distractors with the degree of slowing monotonically related to the shape of distractor distributions. This is indeed what we found in our previous studies 24 28 , 43 . We refer to the test target position in the feature space as the current-target to previous distractor-distance (CT-PD).…”
Section: Methodssupporting
confidence: 93%
“…Our previous experiments indicated that the result from Feature distribution learning cannot be explained by sampling mechanisms where observers encode only a few items from the distribution 25 , 26 . Furthermore, observers’ performance with more complex (bimodal) distributions matched predictions of ideal observer models that accurately represent the distribution shape rather than computing only summary statistics 27 and distribution learning occurred even in the visual periphery 28 . This clearly demonstrated that the visual system encodes feature distribution shape, using it to guide behavior.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In a recent paper, we studied the effect of distractors upon perceptual decisions about the attended items (targets) during visual search for an oddly oriented line among distractors ( Rafiei, Hansmann-Roth, Whitney, Kristjánsson, & Chetverikov, 2021 ). In visual search, observers can surprisingly quickly learn the probability distributions of distractor sets ( Chetverikov, Campana & Kristjánsson, 2016 ; Chetverikov, Campana & Kristjánsson, 2017a ; Chetverikov, Campana & Kristjánsson, 2017b ; Chetverikov, Campana & Kristjánsson, 2017c ; Chetverikov, Campana & Kristjánsson, 2017d ; Chetverikov, Campana & Kristjánsson, 2020a ; Hansmann-Roth, Chetverikov, & Kristjánsson, 2019 ; Hansmann-Roth, Kristjánsson, & Chetverikov, 2020a ; Hansmann-Roth, Kristjánsson, Whitney, & Chetverikov, 2021 ; Tanrıkulu, Chetverikov & Kristjánsson, 2020 ). They can learn which distractor features are more probable than others in surprising detail, and, importantly, unlike the items typically used in serial dependence studies, observers learn to ignore them.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do we seem to be able to generate strong incidental representations, but the memories we have gathered on the fly, during natural interactions, might in fact be critical for proactively guiding our behavior. Chetverikov, Campana, and Kristjánsson ( 2017a ) have shown how repeated searching within search arrays with particular feature distributions of orientation or color (Chetverikov et al, 2017c ; Tanrikulu, Chetverikov, & Kristjánsson, 2020 ) enables observers to learn the probabilities of feature values and build up a probabilistic template of the set for distractor rejection (Chetverikov, Campana, & Kristjánsson, 2020a ). Using a repeated-search task, Võ and Wolfe ( 2012 ) demonstrated that attentional guidance by memories from previous encounters was more effective if these memories were established when looking for an item (during search), compared to looking at targets (explicit memorization and free viewing).…”
Section: Building and Using Behaviorally Optimal Long-term Representationsmentioning
confidence: 99%